Peningkatan Kepatuhan Cuci Tangan melalui Edukasi dan Fasilitasi Hand Hygiene pada Petugas Kesehatan di RSUD Lubuk Basung - Valencia Valencia; Nurmaines Adhyka; Novia Zulfa Hanum; Rendri Bayu Hansah (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
Background: Hand hygiene is an essential component in preventing nosocomial infections in hospitals. Despite global awareness of the importance of hand hygiene, healthcare workers' compliance with hand hygiene protocols remains low. Objective: To improve knowledge and compliance of healthcare workers regarding hand hygiene practices at Lubuk Basung Regional Hospital through education and facilitation programs. Methods: Community service activities were conducted in November 2025 involving 23 healthcare workers from various work units. The program included pre-test, structured education on hand hygiene, demonstration of WHO's 6-step handwashing technique, interactive discussion, post-test, and provision of hand sanitizer facilities and reminder media. Evaluation was conducted by comparing pre-test and post-test scores using a knowledge questionnaire. Results: There was a significant increase in participants' knowledge with an average pre-test score of 80.4% increasing to 92.2% in the post-test (11.8% improvement). A total of 73.9% of participants experienced an increase in knowledge scores. The highest improvement occurred in the Perinatology and MPP units with an increase of 3 points. Conclusion: Education and facilitation programs are effective in increasing healthcare workers' knowledge about hand hygiene. Continuous monitoring and compliance audits are needed to ensure knowledge transfer into real practices in preventing nosocomial infections.